2016
DOI: 10.5194/acp-16-2381-2016
|View full text |Cite
|
Sign up to set email alerts
|

Improved simulation of tropospheric ozone by a global-multi-regional two-way coupling model system

Abstract: Abstract. Small-scale nonlinear chemical and physical processes over pollution source regions affect the tropospheric ozone (O 3 ), but these processes are not captured by current global chemical transport models (CTMs) and chemistryclimate models that are limited by coarse horizontal resolutions (100-500 km, typically 200 km). These models tend to contain large (and mostly positive) tropospheric O 3 biases in the Northern Hemisphere. Here we use the recently built two-way coupling system of the GEOS-Chem CTM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 77 publications
7
34
1
Order By: Relevance
“…Figure 10 compare the spatial distributions of modeled (the control simulation) and observed 2004-2012 average daily, daytime, and nighttime mean ozone over the US. The control simulation overestimates the observed ozone, especially over the eastern US, a common problem in chemical transport models (Fiore et al, 2009;Lin et al, 2008b;Stevenson et al, 2006;Yan et al, 2016;Young et al, 2013). Model biases are about 8.8, 6.3, and 10.4 ppb for the daily, daytime, and nighttime mean ozone, respectively, averaged over the US.…”
Section: Effects Of Emissions and Climate Variability On Ozone Revealmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 compare the spatial distributions of modeled (the control simulation) and observed 2004-2012 average daily, daytime, and nighttime mean ozone over the US. The control simulation overestimates the observed ozone, especially over the eastern US, a common problem in chemical transport models (Fiore et al, 2009;Lin et al, 2008b;Stevenson et al, 2006;Yan et al, 2016;Young et al, 2013). Model biases are about 8.8, 6.3, and 10.4 ppb for the daily, daytime, and nighttime mean ozone, respectively, averaged over the US.…”
Section: Effects Of Emissions and Climate Variability On Ozone Revealmentioning
confidence: 99%
“…php/Main_Page) to simulate the US surface ozone changes over 2004-2012. GEOS-Chem has been used extensively for ozone studies (e.g., Shen et al, 2015;Fu et al, 2015;Yan et al, 2016;Zhang and Wang, 2016). Here, the model is run at a horizontal resolution of 2.5 • long.…”
Section: Model Simulationsmentioning
confidence: 99%
“…Several studies have demonstrated that a better representation of the long-range transport of NO x reservoir species such as peroxyacetyl nitrate (PAN) are important on simulated NO 2 in the free troposphere in remote areas (e.g., Hudman et al, 2004;Fischer et al, 2010Fischer et al, , 2014Jiang et al, 2016). A two-way nesting between regional and coarse-resolution global models (e.g., Yan et al, 2016) is able to consider both small-scale processes inside focusing regions and long-range transport over the globe, which has an advantage over regional models. An important advantage of global high-resolution models over regional models and two-way nesting systems is the ability to simulate NO 2 concentration fields at high resolutions over the entire globe across urban, biomass burning, and remote regions in a consistent framework.…”
Section: Nonlinearity In Model Error Reductionsmentioning
confidence: 99%
“…Meanwhile, the budget terms of global tropospheric O 3 differ significantly between simulations. High-resolution Yan et al (2016), and Williams et al (2017). The latitudinal distributions of O 3 differences between simulations were determined by both chemical (e.g., weakened chemical ozone production in the tropics) and transport (e.g., strengthened downwelling from extratropical stratosphere and upper tropospheric poleward motions from the tropics to the extratropics) processes.…”
Section: Tropospheric No 2 -Related Chemistrymentioning
confidence: 99%
“…Given these limitations, our performance is similar to what some others have obtained (Zhang et al, 2008;Nopmongcol, 2016). However, Zhang et al (2014), who reduced lightning NO x emissions, Travis et al (2016), who reduced lightning and anthropogenic NO x emissions, and Yan et al (2016), who used three two-way nested models within GEOS-Chem, obtained better performance than we did. Fiore et al (2014) also found better performance for GEOS-Chem in their analysis corresponding to Fig.…”
Section: Model Performance For Geos-chemmentioning
confidence: 47%